Pengaruh Rekrutmen, Seleksi, Komitmen Dan Disiplin Kerja Terhadap Produktivitas Karyawan Di Masa Pandemi COVID-19 (Pada Koperasi Unit Desa Kabupaten Pakis Malang) - Irziana Fakhira; Hadi Sunaryo; Eka Farida (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract This study aims to determine 1.) Description of recruitment, selection, commitment, work discipline and employee productivity, 2.) Effect of recruitment, selection, commitment and work discipline on employee productivity, 3.) Effect of recruitment on employee productivity, 4.) Effect of selection on employee productivity, 5.) Effect of commitment on employee productivity, 6.) Effect of work discipline on employee productivity. This research uses quantitative methods with descriptive and inferential analysis. The number of samples used was 33 employees at the Village Unit Cooperative Pakis, Malang Regency. Sources of data used are primary and secondary data sources. The data were collected using a questionnaire with a Likert scale measurement while the data analysis used was instrument test, classical assumption test, multiple linear regression analysis, hypothesis testing, and the coefficient of determination (R2) with SPSS 16.0 as a tool. The results showed that 1.) Recruitment, selection, commitment, and work discipline have a simultaneous influence on employee productivity, 2.) Recruitment has an influence on employee productivity, 3.) Selection has an influence on employee productivity, 4.) Commitment has no effect. influence on employee productivity, 5.) Work discipline has an influence on employee productivity. Keywords: Recruitment, Selection, Commitment, Work Discipline and Employee Productivity.